Self-esteem and academic resilience of student organization’s functionaries: Changes in academic development. - Devi, Karisma Chandra; Huwae, Arthur (Universitas Islam Negeri Raden Intan Lampung, 2023)
Engaging in organizational activities fosters individual growth; nonetheless, active participation necessitates individuals to invest their time, energy, cognitive effort, perseverance, and motivation. This correlational study aims to examine the relationship between self-esteem and academic resilience among student council functionaries in vocational high schools in Salatiga. By employing the quota sampling technique, a total of 143 student councils functionaries from six vocational high schools were recruited as participants Data were collected using the Self-esteem Inventory and the Academic Resilience Scale (ARS-30) and analyzed utilizing the Pearson Product Moment correlation coefficient. The result demonstrated a positive, significant relationship between self-esteem and academic resilience (r = 0.363 α= 0.000). In other words, self-esteem emerges as a contributing factor to increased academic resilience among student council functionaries in vocational high schools in Salatiga. It is necessary for the schools to provide a problem-solving-based program to improve the self-esteem of students engaging in student council activities. Having a higher level of self-esteem, students will likely possess higher academic resilience.